Study of spatial and temporal variations of the Buktyrma River bank erosion - Talgat R. TAUKENOV; Zhuldyz S. YERZHANOVA; Kulchikhan M. DZHANALEEVA (European Journal of Geography)
This study addressed the causes, mechanism and different forms of bank erosion of the Buktyrma River near to human settlements; their dependence on the morphology of banks, connection with river channel deformations is clearly shown. For this purpose, multi- temporal space images and cartographic materials were used. The calculation of the horizontal deformations of the riverbed was performed by GIS. When modeling channel processes, the following data was used: space images RapidEye, Landsat and Sentinel -2 for the period from 1975 to 2017, topographic maps 1960-1980, data of geodetic surveys 1965- 2010, digital elevation model SRTM 2000, field observations at coastal destruction sites for 2011-2017, geological map of 1979 and geomorphological map of 2010. Based on SRTMdigital elevation model drawn map showing the river systems of the structure, characteristics and hypsometric Buktyrma catchment area of the river. The article shows examples of identifying scouring river banks by space images near 5 settlements - Kaiyndy, Shyngystai,Bykovo, Parygino and Turgusun. A hydromorphological analysis of the channel and erosion processes in selected sections of the river was carried out, and the causes of the channel changes were identified. The article also provides examples of creating schemes for eroded parts of the Buktyrma river, highlighting spatial changes of erosion near the villages of Parygino and Turgusun. Recommendations have been elaborated for the improvement of the existing system through which erosion processes are monitored.